Trilemma in Court: The Shari’a Court in Beer-Sheva as a Convergence Point of Three Law Systems - Shahar, Ido (Jama’a: an Interdisciplinary Journal of Middle East Studies, 1997)
The two main approaches to legal anthropology are lacking in their analysis of the interplay between varying legal systems. Based on "participant observations" at the Shar’ia court in Beer Sheva, this article analyzes court situations that emphasized the unique interaction between three different legal systems: Israeli civil law, Islamic Shar’ia law, and Bedouin custom (Urf). These legal systems represent three different worldviews distinguished from each other on the micro level (the meeting of the actors who operate in the court: the Qadi, the shar’i counsels and the litigants), and חס the macro level (internal and external social processes occurring within Bedouin society and working to integrate it into the wide Israeli society). The incongruity of these three legal systems is utilized by Bedouin litigants; what is more, the appeal (or even the threat of appealing) to the Shar’ia court constitutes an effective social resource in diverse conflicts.